2022
DOI: 10.1055/s-0042-1747910
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Age and Middle Ear on the Frequency Tuning of the cVEMP and oVEMP

Abstract: Background Upward shift in the air conducted (AC) frequency tuning of vestibular evoked myogenic potentials (VEMPs) as an effect of aging is hypothesized to be due to the microstructural stiffening changes in the inner ear. However, with an AC stimulus, it may be possible that the shift in the frequency tuning of VEMPs as an effect of aging may also be due to contributions from the middle ear. Purpose The main aim of this study was to examine the effects of age on the frequency tuning of the cervical… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Nevertheless, since the middle ear resonant frequency of healthy adults was reported to be in a range of 800–1200 Hz 41 , 47 , it is expected that this effect is negligible (which is supported by the comparable P1–N1 amplitude values produced by the two stimuli in this meta-analysis). In accordance with this, a study carried out by Jha et al revealed that differences in the “best” frequency of cVEMP between young and old adults were not significantly attributed to the middle ear factor 48 .…”
Section: Discussionmentioning
confidence: 55%
“…Nevertheless, since the middle ear resonant frequency of healthy adults was reported to be in a range of 800–1200 Hz 41 , 47 , it is expected that this effect is negligible (which is supported by the comparable P1–N1 amplitude values produced by the two stimuli in this meta-analysis). In accordance with this, a study carried out by Jha et al revealed that differences in the “best” frequency of cVEMP between young and old adults were not significantly attributed to the middle ear factor 48 .…”
Section: Discussionmentioning
confidence: 55%